Digital Storytelling: A Technological Approach - Katherine E. Perone (The University of Alabama, 2022)
Review of the book: Digital Storytelling: Capturing Lives, Creating Community. Joe Lambert. Routledge: New York, N.Y., 2013, 206 pages, ISBN: 978-0-415-62703-0